The Effects Of The Passıve Posterıor Bıte-Block And The Vertıcal Chın-Cap On The Vertıcal Dımensıons Of The Face And The Dentoalveolar Structures In The Treatment Of Skeletal Open-Bıte - Elçin Koralp Gür; Hakan N. İşcan (Galenos Yayinevi, 1991)
The purpose of this study was to examine the effects of the passive posterior bite-block and the vertical chin-cap on the vertical dimensions of the face and the dentoalveolar structures in early treatment of skeletal open-bite. Forty-one subjects −19 treatment 22 control group-having skeletal and dental open-bite and having skeletal and dental Class 1 or Class 2 malocclusion were observed for a period of 8 months. The study was carried out on 82 lateral cephalometric films and hand-wrist radiographies. The mean age of the treatment group was 10 years 3 months, and 10 years 8 months in the control group. During the study period mandibular plane angle, maxillo-mandibular angle, joint angle, lower face height, lower and upper incisal teeth inclinations and the lower posterior dentoalveolar height decreased in the treatment group, that were found to be statistically significant when compared to the control group. In the treatment group a forward and upward mandibular rotation was achieved by the use of posterior bite-block and vertical chin-cap.